Recent advances in JAK inhibitors for the treatment of metabolic syndrome - Collotta, Debora; Franchina, Maria Paola; Carlucci, Virginia; Collino, Massimo (Frontiers in Pharmacology, 2023)
With an epidemic spread, metabolic syndrome represents an increasingly emerging risk for the population globally, and is currently recognized as a pathological entity. It is represented by a cluster of different conditions including increased blood pressure, high blood sugar, excess body fat around the waist and abnormal cholesterol or triglyceride levels. These conditions lead directly to several disorders, including obesity, dyslipidemia, hyperglycaemia, insulin resistance, impaired glucose tolerance and hypertension causing an increase in cardiovascular risk and in particular atherosclerotic disease. Despite efforts to promote healthier lifestyles through exercise, reduced caloric intake, and improved dietary choices, the incidence and prevalence of metabolic syndrome continue to rise worldwide.Recent research has highlighted the involvement of signaling pathways in chronic inflammatory conditions like obesity and type 2 diabetes mellitus, revealing the significance of the JAK/STAT pathway in atherosclerotic events. This pathway serves as a rapid membrane-to-nucleus signaling module that regulates the expression of critical mediators. Consequently, JAK inhibitors (JAKi) have emerged as potential therapeutic options for metabolic diseases, offering a promising avenue for intervention.The aim of this review is to shed light on the emerging indications of JAK inhibitors in metabolic syndrome, emphasizing their potential role in attenuating associated inflammatory processes, 2 This is a provisional file, not the final typeset article improving insulin sensitivity, and addressing cross-talk with the insulin pathway, with the intention of contributing to efforts in the field of inflammation pharmacology.